A robust platform to construct molecular patchy particles with a pentiptycene skeleton toward controlled mesoscale structures. Issue 15 (29th March 2022) - Xu, Wei; Wang, Yicong; Guo, Qing-Yun; Wang, Xiaoteng; Liu, Yuchu; Bian, Feng-Gang; Yan, Xiao-Yun; Ni, Bo; Cheng, Stephen Z. D.
Abstract : A new pentiptycene skeleton with orthogonally reactive sites and inherent  D 2h -symmetry to construct molecular pathy particles toward mesoscale structures. Abstract : Patchy particles with novel architectures and diverse applications have attracted significant attention in recent years. Nevertheless, the synthesis of well-defined nanosized patchy particles with a precise structure remains a challenge. Herein, using a pentiptycene-based skeleton with D 2h -symmetry, we constructed molecular patchy particles with a defined symmetry and diverse patch interactions via tethering functionalities at two sets of orthogonally reactive sites ( i.e., eight alkyne sites at the peripheral position and two hydroxyl groups at the para -position of the central phenyl ring). As a demonstration, patchy particles containing fluorocarbon chains at the peripheral position and two polystyrene patches at the para -position were found to self-assemble into a series of well-defined nanostructures upon varying the compositions of the patches at the para -position. The exploration of pentiptycene derivatives not only enriches the family of molecular patchy particles, but also provides a versatile platform to transform the molecular structures to mesoscopically assembled morphologies.